Contribution of biomotor and psychomotor factors that determine Pencak Silat Front Kick ability - Yusuf Panjiantariksa; Muchsin Doewes; Tri Aprilijanto Utomo (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
This study aims to determine the contribution of biomotor and psychomotor factors that determine pencak silat front kick ability. The study uses quantitative methods and confirmatory factor analysis design. This type of research used in this research is correlational research with confirmatory factor analysis design that confirms the relationship of indicator variables with latent variables that determine the ability of the front kick pencak silat. Data collection is processed and analyzed using a computer-based application Statistics SPSS (Product Statistics and Service Solutions) Version 23 and using the Kaiser-Meyer-Olkin test and Bartlett Test. The sample is a part or representative being studied. As a sample it is better to have the same characteristics as a population so that you can draw a picture of the population. The population and sample in this study were all students fostering the achievement of Pencak Silat UKM PSHT Sebelas Maret University with a total of 25 students. The sampling technique used was purposive sampling.The technique in collecting data uses tests and measurements. The results of the study are as follows: analysis of biomotor and psychomotor factors that determine the ability of the pencak silat front kick above, the biomotor and psychomotor factors that determine the ability of the front kick of pencak silat (H0 accepted) or those that have a factor component value of ≥ 0.5 are: Biomotor and psychomotor factors that contribute to determining the ability of pencak silat front kicks 1. Power of leg muscles with a factor component value of 0.92 2. Flexibility with a factor component value of 0.43 3. Power the abdominal muscles with a factor component value of 0.53 4. The balance with the factor component value is 0.91 5. Agility with a factor component value of 0.24 The results of the statistical analysis of biomotor and psychomotor factors that contribute to determining the ability of the front kick of pencak silat are leg muscle power (0.92), balance (0.91), abdominal muscle power (0.53), flexibility (0.42), and agility (0.24).